The Effectiveness of The Indonesian Ombudsman in Managing The Administration during The Covid-19 Pandemic - Ismail, Nurwaqiah; Safriani, Andi; Asmar, Abd. Rais (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to evaluate the effectiveness of the Ombudsman in handling cases of maladministration in the midst of the Covid-19 pandemic and identify obstacles and efforts in the handling process. Through a qualitative approach with primary and secondary data sources, the results showed that the effectiveness of handling maladministration by the Ombudsman of the Republic of Indonesia representing South Sulawesi decreased during the pandemic. This was due to the adoption of the Work from Home Policy and the implementation of the PSBB, which resulted in delays in the completion of the report. The Ombudsman took steps such as requesting written clarification from the reported Party and opening a Covid-19 complaint post in an effort to make it easier for the public to report suspected maladministration without having to interact directly to prevent transmission of the virus.